2021
DOI: 10.3389/frwa.2021.661662
|View full text |Cite
|
Sign up to set email alerts
|

How Does Residential Property Market React to Flood Risk in Flood-Prone Regions? A Case Study in Nagoya City

Abstract: To quantify the flood risk awareness of real estate market participants and residents, previous studies analyzed the effect of flood risks on residential property values. However, most studies focused on the impact of recent flood events and the publication of new flood risk information; the behavior in flood-prone regions in which repeated damages occurred and lessons learned consequently has not been the focus of analysis. Moreover, there is a growing national concern in Japan about an increase in future flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Participants in this study clearly indicated that they want access to flood risk information in the form of flood maps and mandatory property disclosure concerning flood risk. The fact that these respondents support these tools, despite living in designated flood risk areas, appears to challenge the notion in previous scholarship that homeowners will resist the release of this information out of fear of the potential consequences to their home value (e.g., Bakos et al 2022 ; Inoue and Hatori 2021 ).…”
Section: Social Acceptability Of Policy Instruments For Flood Risk Ma...mentioning
confidence: 67%
See 1 more Smart Citation
“…Participants in this study clearly indicated that they want access to flood risk information in the form of flood maps and mandatory property disclosure concerning flood risk. The fact that these respondents support these tools, despite living in designated flood risk areas, appears to challenge the notion in previous scholarship that homeowners will resist the release of this information out of fear of the potential consequences to their home value (e.g., Bakos et al 2022 ; Inoue and Hatori 2021 ).…”
Section: Social Acceptability Of Policy Instruments For Flood Risk Ma...mentioning
confidence: 67%
“…On the other hand, adoption of this instrument set would place new controls on real estate transactions that the public might perceive as intrusive. Moreover, disclosure of flood risk information is often perceived to have negative impacts on property values (Inoue and Hatori 2021 ; Votsis and Perrels 2016 ) and liability is difficult to discern due to uncertainty around the causes and timing of flooding.…”
Section: Frm Policy Instrumentsmentioning
confidence: 99%
“…The second method compares housing prices before and after a flood (Miller and Pinter, 2022;Atreya and Ferreira, 2015). However, Inoue and Hatori (2021) find that the occurrence of new floods does not affect the prices of houses located in frequently flooded areas because the price already incorporates flood conditions. Therefore, we choose the last method for our study -HPM.…”
Section: Literature Reviewmentioning
confidence: 99%